The syncretic strategies of the miniseries Suburbia - Santana, Gelson (2016)
The miniseries Suburbia, directed by Luiz Fernando Carvalho (Globo Television Network, 2012), turns the concept of pre-logical into a way to expose the multiple audiovisual aspect. The miniseries blends temporalities, causes a lack of definition between fiction and reality, and, through Roberto Carlos’ ballads, emphasizes the dimensions of affection and faith in a community of Rio de Janeiro. Some points of the miniseries clarify the syncretic way that the narrative was shaped in and assess the possibility of a new trend to be explored in Brazilian television fiction. The analytical instruments are based in Raymond Bellour, the narrative examination is based in Kristin Thompson, and the idea of oral pre-logic cultures in Lévy-Bruhl